Clinical profile of congenital heart disease in children with special reference to echo correlation - Patra, Upasana; Agarwalla, Sunil Kumar; Das, Bharati (International Journal of Contemporary Pediatrics, 2023)
Background: Congenital heart disease (CHD) is the most frequently occurring congenital disorder responsible for 1/3rd of all congenital birth defects. Diagnostic accuracy of CHD is crucial for timely intervention and optimal patient outcome. So, the study has been done to look for the clinical profile and establishing correlation of clinical diagnosis with echocardiography diagnosis. Methods: This is a prospective cross-sectional study conducted in the department of pediatrics MKCG MCH, Berhampur over a period of 2 years. All children between 1 month to 14 years admitted for suspected CHD were included in the study. Clinical diagnosis was made based on detailed history and physical examination supported by chest X-ray and ECG. Final diagnosis was confirmed by echocardiography and clinico-ECHO correlation was deduced. Results: The 188 patients with CHD were included in this study. The most common age of presentation was 1 month to 1 year with 71.2%, male to female ratio was 1.06:1. Acyanotic CHD (ACHD) was found to be 70.29%, while 29.7% had congenital cyanotic heart disease (CCHD). Clinically specific diagnosis was attributed to 67.1% of cases and no specific diagnosis could be made in 32.9%. Isolated CHD was found to be 66.4% and Complex CHD with multiple defects was found to be 33.6%. Clinic echo correlation was accurate in 39.4% cases, partially correlated in 32% and no correlation in 28.6% cases. Conclusions: So, echocardiography remains the gold standard for diagnosis of CHD and guiding the treatment. Clinical diagnosis alone may not detect associated CHD.